Invertebrados bentónicos en el Mar Argentino: estado actual de conocimiento, riqueza específica y patrones de distribución. - Souto, V. (Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales, 2014)
The assessment of biodiversity is important to understand the ecological patterns of species distribution as well as the functioning of ecosystems, and to manage the use of marine resources and conservation. The aim of this thesis was to compile and analyze available historical information on hydroids, polychaetes, decapod crustaceans and echinoderms in the South Western Atlantic Ocean, between 34° and 56° S, in order to make a synthesis of present taxonomical knowledge, to identify patterns of geographical distribution assemblages and to test the validity of the current zoogeographic scheme established for the study area. Multivariate analysis was used to analyze the faunal composition through latitudinal and bathymetric gradients as well as for identifying different associations of benthic invertebrates. The species richness recorded was high for all groups and in all cases a certain number of species was considered of doubtful validity, consequence of the spatial-temporal discontinuity of their records. The species richness in echinoderms and polychaetes increases significantly towards higher latitudes, which could be related with the high diversity of these groups in the Antarctic Region. This correlation was not significant for hydroids, however, areas where the richness reached high values that could be related to the presence of suitable substrates for their successful settlement were identified. Decapod crustaceans did not exhibit any pattern in relation to latitude. Though, a pattern of decline in species richness at high latitudes has been cited for this group. The results confirmed the existence of two faunal associations that correspond to the traditional zoogeographic scheme established for the Argentine Sea: the Argentinean and Magellan Provinces. The results also indicate that the Argentinean Province includes San Jorge Gulf (45° – 47° S). La evaluación de biodiversidad es importante para la comprensión de los patrones ecológicos de distribución de especies, para comprender el funcionamiento de ...